Caracterización físico química del suelo en dos pisos altitudinales, dedicados a la producción orgánica de café (Coffea arabica L.), en la parroquia Zumba, cantón Chinchipe - Abad Cordero, Pablo Andrés (2023)
ACRIM, set down in the Zumba community, it contributes to improving the economy of the Chinchipe town, through the production and coffee sells. The low production (0,30 t.ha-1) is worrying compared with other countries such as Colombia and Brazil, which reach production of 5,70 and 6,73 t.ha-1. These yields are attributed to the acidity and low availability in the soil nutrients. The research had aimed the organic coffee production (arabica coffee L.) through the physical and chemical soil characterization to determine its fertility and generate a fertilization plan to increase the grow yield. As a result, it was obtained that the highest income comes from coffee growing, with a production of 0,48, 0,61 and 0,69 t.ha-1 for small (0 to 2 ha), medium (2 to 5 ha) and big producers (5 to 10 ha). The physicochemical soil characteristics at the Finca el Pino are: texture FoAo, Dap= 1,08 g.cm-3, pH 4,6, Al+3 equal to 4,94, low in K, S and B; and a half in P, Ca and Mg. Finca Altavista has a texture FoAc, Dap= 1 g.cm-3, pH 5,6, Al+3 equal to 0,55, low in P and B; and a half in S. To neutralize the acidity the ration was used. 1 meq of Al equal to 0.5 meq of Ca, and the fertility plan was elaborated with the requirement of the coffee, supported by studies of biological evaluation carried out in Amazon Ecuadorian soils. Keywords: Characterization, physical, chemical, Amendment, organic coffee, ACRIM.